Definiowanie pojęć w prawie podatkowym jako ograniczenie obszaru nieostrości - Borszowski, Paweł (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
The article discusses the problem of defining terms in tax law. One of the bases for introducing these definitions is to limit the blurring of definitions. This is the basis for the definition of the relationship between them and the terms outlined.The purpose of the study is to indicate the determinants of the limitation of the blur. They are also the determinants of the introduction of legal definitions.The analysis of these determinants with the avoidance clause leads to the conclusion that the determinants need to be looked for.
Keywords: definicje prawne; rozmycie obszaru; wyznaczniki